Periodontal conditions in patients with Sjögren's syndrome: A meta-analysis - Shih-Yun Wu; Ching-Yi Wu; Ming-Han Chen; Hsin-Yi Huang; Yu-hsuan Chen; Yen-Po Tsao; Yu-Lin Lai; Shih-Yuan Lee (Elsevier, 2021)
Sjögren's syndrome (SS) is a chronic autoimmune rheumatic disease characterized by a progressive lymphocytic infiltration of salivary glands, resulting in xerostomia and other oral diseases. The pathogenesis and mechanisms of SS on periodontal tissues are not well understood. Furthermore, results of two systemic reviews and meta-analyses in which compared periodontal parameters of patients with SS to healthy subjects were different. To determine whether periodontal conditions in SS were different from healthy controls, we re-examined the issue with a random-effect model, avoiding recruiting active controls and inadequate data conversion. Outcome measures included probing pocket depth (PPD), clinical attachment loss (CAL), plaque index (PI), and gingival index (GI). Recruited individuals comprised 198 patients with SS and 180 subjects for healthy controls. Quantitative analysis revealed higher PI (WMD = 0.76, 95% CI: 0.30, 1.23) and GI (WMD of total = 0.50, 95% CI: 0.01, 0.98) in SS patients who were not categorized into primary or secondary types of SS. PPD and CAL in SS patients was comparable with control subjects. However, heterogeneity was observed among included studies. Thus, results from this and previous analyses should be interpretated carefully, and a well-designed observational study regarding this issue should be conducted.